Applying MDA and OMG Robotic Specification for Developing Robotic Systems - Pons, Claudia Fabiana (2016)
Robotics systems have special needs often related with their realtime nature and environmental properties. Often, control and communication paths within the system are tightly coupled to the actual physical configuration of the robot. As a consequence, these robots can only be assembled, configured, and programmed by robot experts. Traditional approaches, based on mainly writing the code without using software engineering techniques, are still used in the development process of these systems. Even when these robotic systems are successfully used, several problems can be identified and it is widely accepted that new approaches should be explored. The contribution of this research consists in delineating guidelines for the construction of robotic software systems, taking advantage of the application of the OMG standard robotic specifications which adhere to the model-driven approach MDA. Thereby the expert knowledge is captured in standard abstract models that can then be reused by other less experienced developers. In addition part of the code is automatically generated, reducing costs and improving quality.